The scale of the indigenous body in internal displacement forced by violence - Arellano Hidalgo, Erandy Anaid (2025)
Forced internal displacement has effects at the local and national scale; however, one of the scales that is affected in the first instance and in the process of displacement itself, is the scale of the body. The aim of this article is to analyze the implications that forced internal displacement has on the scale of the body. The methodological perspective that we follow is qualitative, the collection of information was carried out through semi-structured interviews and some notes that are part of the research on forced internal displacement of triquis indigenous people in Mexico City. The article concludes that the body is the first affected when the displacement takes place, as well as during the entire process that follows after the moment in which it is displaced.